UN Women/FAO/IFAD/WFP Expert group meeting (Sept. 2017) summary report - van Koppen, Barbara (International Water Management Institute, 2017)
Presented by Barbara van Koppen (IWMI), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.)